2022
DOI: 10.1038/s41598-022-16446-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breathing promotes lung injury in an experimental model of alveolar collapse

Abstract: Vigorous spontaneous breathing has emerged as a promotor of lung damage in acute lung injury, an entity known as “patient self-inflicted lung injury”. Mechanical ventilation may prevent this second injury by decreasing intrathoracic pressure swings and improving regional air distribution. Therefore, we aimed to determine the effects of spontaneous breathing during the early stage of acute respiratory failure on lung injury and determine whether early and late controlled mechanical ventilation may avoid or reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, assisted ventilation led to profound hypoxemia in most of the patients who failed, which albeit hypothetical in nature, could have modified the patient’s clinical course. Bachmann et al observed persistent severe hypoxemia in ARDS models undergoing PSV even after 4 hours of a recovery period under protective MV ( 41 ). Similarly, we observed wide NMBAs and prone requirements after failure due to severe hypoxemia, which unfaithfully delayed ventilator weaning and prolonged MV.…”
Section: Discussionmentioning
confidence: 99%
“…However, assisted ventilation led to profound hypoxemia in most of the patients who failed, which albeit hypothetical in nature, could have modified the patient’s clinical course. Bachmann et al observed persistent severe hypoxemia in ARDS models undergoing PSV even after 4 hours of a recovery period under protective MV ( 41 ). Similarly, we observed wide NMBAs and prone requirements after failure due to severe hypoxemia, which unfaithfully delayed ventilator weaning and prolonged MV.…”
Section: Discussionmentioning
confidence: 99%
“…In a healthy lung, however, the pulmonary surfactant system not only reduces but also harmonizes surface tension in the alveoli, so that alveoli of different sizes can co-exist and stress concentration is avoided ( Schürch, 1982 ; Schirrmann et al, 2010 ). Low volume mechanical ventilation or spontaneous breathing in presence of stress concentrations, such as microatelectases or flooded alveoli, results in injury of the blood-gas barrier and degradation of lung mechanics, despite no increase in strain at the organ level ( Wu et al, 2014 ; Albert et al, 2020 ; Krischer et al, 2021 ; Bachmann et al, 2022 ). High tidal volume ventilation with low positive end-expiratory pressure produces progressive ventilation-induced lung injury with severe damage of the blood-gas barrier in mice ( Hamlington et al, 2018 ).…”
Section: Respiration Related Deformation Of the Lung Parenchyma: Visu...mentioning
confidence: 99%
“…Although evidence from experimental and clinical studies suggests that P-SILI is a severe and life-threatening clinical condition, intensivists have no consensus on when to intubate a patient with excessive respiratory effort. In animal studies with artificially induced lung injury, early use of mechanical ventilation eventually led to less severe lung injury than leaving them to ventilate spontaneously with vigorous effort, and mechanical ventilation prevented self-inflicted lung injury if applied early but not when applied late [6,7,67,68]. Some authors, therefore, advocate that in the context of high respiratory drive and vigorous respiratory effort, mechanical ventilation with lung-protective parameters might be considered a protective therapy to minimize P-SILI [5,69].…”
Section: Prevention and Treatment Of P-silimentioning
confidence: 99%